High-performance all-polymer dielectric and electrical energy storage materials containing conjugated segment and multi-fluorinated pendants. (5th January 2020) - Han, Huijing; Zhou, Dandan; Ren, Qianyi; Ma, Fengwang; Ma, Cuihong; Xie, Meiran
Graphical abstract: Highlights: Block copolymer containing multi-fluorinated segments was synthesized. Block copolymer displayed dielectric constant of 8 and dielectric loss of 0.002. Block copolymer exhibited energy density of 11.45 J cm −3 and efficiency of 99%. Abstract: Highly polarizable block copolymer consisting of insulating polynorbornene and conductive polyacetylene segments with multi-fluorinated pendants was synthesized by tandem ring-opening metathesis polymerization and metathesis cyclopolymerization, which displayed relatively high dielectric constant of 8, very low dielectric loss of about 0.003, and enhanced energy density of 11.45 J cm −3 at the electric field strength of 450 MV m −1 accompanied with an excellent charge-discharge efficiency of 99%. The outstanding dielectric and energy storage capability were mainly attributed to high dipole moment of multi-fluorinated groups on polymer backbone and the interfacial polarization derived from the unique self-assembled nanostructure of block copolymers.